Neurosurgery: A Silk Cranial Fixation System for Neurosurgery (Adv. Healthcare Mater. 6/2018). Issue 6 (25th March 2018) - Liu, Keyin; Shi, Zhifeng; Zhang, Shaoqing; Zhou, Zhitao; Sun, Long; Xu, Tao; Zhang, Yeshun; Zhang, Guozheng; Li, Xinxin; Chen, Liang; Mao, Ying; Tao, Tiger H.
Abstract : In article number 1701359, Ying Mao, Tiger H. Tao, and co‐workers report on the silk cranial fixation system. The system includes silk screws and strips to anchor the bone flap, which are fabricated from natural silk proteins obtained from cocoons of the Bombyx mori silkworm. The system is used to provide a protective shield to brain after neurosurgery.